Endoscopic resection using the Clutch Cutter and a detachable snare for large pedunculated colonic polyps - Akahoshi, Kazuya; Kubokawa, Masaru; Gibo, Junya; Osada, Shigeki; Tokumaru, Kayo; Shiratsuchi, Yuki; Oya, Masafumi; Ihara, Eikichi; Nakamura, Kazuhiko (Endoscopy, 2017)
Background and study aims Endoscopic snare polypectomy with prophylactic detachable snare of large pedunculated colonic polyps (PCPs) is technically demanding. To facilitate removal of such polyps, we developed endoscopic resection using the Clutch Cutter and a detachable snare (ERCCDS). This study aimed to evaluate the efficacy and safety of the procedure.Patients and methods From April 2010 to July 2015, 14 consecutive patients who had PCPs with head > 10 mm, stalk width > 5 mm, and stalk length > 10 mm were enrolled in this single-center prospective uncontrolled study. They were treated using ERCCDS by a single endoscopist. The efficacy and safety were assessed using a database prospectively formatted from the medical records.Results The Clutch Cutter was able to cut the distal side of the stalk an adequate distance from the detachable snare under good visual control. R0 resections were obtained in all lesions. There were no immediate or delayed complications. Conclusions ERCCDS appears to be a safe, easy, and technically efficient method for large PCPs, although larger studies are needed to compare ERCCDS and standard resection.